2021
DOI: 10.3389/fpubh.2021.738423
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Incidence and Mortality by Age Strata and Comorbidities in Mexico City: A Focus in the Pediatric Population

Abstract: Background: SARS-COV2 appears less frequently and less severely in the pediatric population than in the older age groups. There is a need to precisely estimate the specific risks for each age group to design health and education policies suitable for each population.Objective: This study aimed to describe the risk of death in SARS-COV2 infected subjects by age group and according to the presence of comorbidities.Methods: We analyzed data of confirmed SARS-COV2 infection cases where symptoms began between Febru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 12 publications
4
18
0
1
Order By: Relevance
“…On the contrary, there is evidence showing that pediatric asthma has no impact or even plays a protective role against the development of severe SARS-COV-2 infection. Cohort studies from the UK and Mexico found no significant association between asthma and hospital admission in pediatric patients [7,162]. In addition, in a study involving more than 19,000 COVID-19 patients who presented to the emergency department (ED) across 45 US children's hospitals, asthma was found to be associated with an increased risk of hospitalization, compared to pediatric COVID-19 patients discharged from the ED.…”
Section: Asthmamentioning
confidence: 99%
“…On the contrary, there is evidence showing that pediatric asthma has no impact or even plays a protective role against the development of severe SARS-COV-2 infection. Cohort studies from the UK and Mexico found no significant association between asthma and hospital admission in pediatric patients [7,162]. In addition, in a study involving more than 19,000 COVID-19 patients who presented to the emergency department (ED) across 45 US children's hospitals, asthma was found to be associated with an increased risk of hospitalization, compared to pediatric COVID-19 patients discharged from the ED.…”
Section: Asthmamentioning
confidence: 99%
“…In children under 10 years of age, comorbid conditions associated with increased mortality were mainly those coded as ‘other comorbidities’. In those between 11 and 20 years old, diabetes, obesity, immunosuppression and chronic renal disease were the most significant associated factors 49…”
Section: Discussionmentioning
confidence: 99%
“…In those between 11 and 20 years old, diabetes, obesity, immunosuppression and chronic renal disease were the most significant associated factors. 49 …”
Section: Discussionmentioning
confidence: 99%
“…Concerning the Latin-American population, high fatality rates have been observed in Hispanics Specifically in Mexican patients, there have been some attempts to define the factors associated with COVID-19 severity and mortality. The presence of obesity, diabetes, hypertension, and CKD increases the mortality risk of COVID-19 [ 2 , 19 , 20 ], the mortality risk sharply increases with two or more comorbid diseases [ 19 ]. The Mexican population is at high risk of developing severe COVID-19 due to the high prevalence of overweight, with 70% of the population being overweight [ 21 ].…”
Section: Discussionmentioning
confidence: 99%